Two-stage amplifier design based on experimental Line-Tunnel FET data - Filho, Walter Gonçalez; Martino, Joao A.; Rangel, Roberto; Agopian, Paula G. D. [UNESP]; Simoen, Eddy; Rooyackers, Rita; Claeys, Cor; Collaert, Nadine (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This work presents for the first time a two-stage operational transconductance amplifier (OTA) design based on experimental Line-TFET devices. To account for different parasitic effects, make the project more feasible and avoid complicated and inaccurate analytical modelling, experimental devices are measured and the data is used in lookup tables to be coded in Verilog-A hardware description language. A two-stage amplifier is designed considering the particularities of these devices and the figures of merit achieved are related to its characteristics, including the non-idealities verified in the experimental characterization. The designed amplifier exhibits extremely high open loop voltage gain, good performance and bandwidth when compared with other TFET designs, at moderate power supply voltage with high output swing and low power consumption. The results obtained are compared with MOSFET designs and with other TFET based amplifiers found in the literature.
Keywords: analog circuit design; Line-TFET; two-stage amplifier